(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
The court decision: ‘ENFORCEMENT OF EXTRAJUDICIAL TITLE. VIRTUAL DUPLICATE. PROTEST BY INDICATION. BANK SLIP ACCOMPANIED BY PROOF OF RECEIPT OF GOODS. NO NEED FOR JUDICIAL EXHIBITION OF THE ORIGINAL CREDIT DOCUMENT. 1. Virtual bills of exchange - issued and received by magnetic means or electronic recording - can be protested by mere indication, so that it is not essential to show the bill of exchange in order to file for judicial enforcement. Law 9.492/97. 2. The bank collection slips linked to the virtual security, duly accompanied by the instruments of protest by indication and proof of delivery of the goods or provision of the services, compensate for the physical absence of the electronic and constitute, in principle, extrajudicial executive titles. 3. Special appeal dismissed.’ (STJ, REsp nº 1.024.691-PR, 3rd Panel, Rel. Min. Nancy Andrighi, Date of Judgement: 22/03/2011, DJe 12/04/2011)